An analysis of the rebuilding of Rotterdam after the bombing on May 14, 1940 - Runyon, David (My University, 1969)
Contents include: a brief history of Rotterdam, expropriation and its implications, analysis of the inner city: traffic generators, analysis of the inner city: edges, analysis of the inner city: business behavior and pedestrian generators, analysis of the inner city: cooperation, analysis of the inner city: problem areas, and a brief history of town planning (housing and parks) as it relates to Rotterdam.
146, [58] leaves : ill. (some col.), maps ; 29 cm.
Keywords: City planning --Netherlands --Rotterdam.